Contextual Learning Development in Schools through the Integration of Batak Toba Local Wisdom from Sibandang Island - Firmando, Harisan Boni; Panjaitan, Ade Putra Arif; Sibarani, Robert; Simbolon, Elvri Teresia; Telaumbanua, Eben Haezarni; Saragih, Ratna (LP. Ma'arif Janggan Magetan, 2024)
The integration of local wisdom in education is a crucial effort in the development of contextual learning in Indonesia, particularly in preserving and actualizing cultural values such as those of the Batak Toba community. This study aims to examine how the values of Batak Toba local wisdom can be integrated into contextual learning in schools. Using a qualitative approach through a literature review, this research involved a thematic analysis of scientific sources—including journals, academic books, and relevant research reports—published over the last two decades. The inclusion criteria focused on literature discussing local wisdom, character education, and curriculum development in the Indonesian context. The findings reveal that Batak Toba local wisdom contains rich educational values such as dalihan na tolu, mutual respect, communal harmony, and spiritual beliefs that can enrich classroom instruction, foster character development, support the implementation of the Kurikulum Merdeka, and enhance students’ cultural literacy. These values, when integrated into learning, not only make education more meaningful and rooted in students’ realities but also strengthen national identity in a multicultural society. The study concludes that integrating Batak Toba local wisdom into school-based learning is an urgent and strategic step to ensure that education in Indonesia remains culturally grounded, ethically formative, and responsive to the needs of future generations. This research contributes to the discourse on culturally relevant pedagogy and opens new pathways for designing educational models that harmonize local heritage with national educational goals.